Pengaruh Latihan Passing Menggunakan Target Permainan Terhadap Hasil Passing Sepakbola - Mohamad Rizqi Aprianto; Sri Maryati; Ruli Sugiawardana; Dede Iman Suhendra (Universitas Galuh, 2023)
The purpose of the research that the author proposes is to determine whether there is a significant influence of passing training using game targets on football passing results at SMK Galuh Rahayu. The research method used in this study is pre-experimental designs, This research design uses a one-group pretest-posttest design. The population in this study were students who took extracurricular activities totaling 20 children. The sample in this study was 20 students. Based on the results of the paired t-test, it can be concluded that: Sig. Value (2-tailed): 0.000, which is smaller than 0.05. Decision: Because the probability (0.000) <0.05, then Ho is rejected and Ha is accepted. The conclusion is that there is a significant influence of passing training using game targets on football passing results at SMK Galuh Rahuya, meaning that passing training using game targets is effective in improving football passing results. Based on the results of the research and hypothesis testing, it can be concluded that: